2000
DOI: 10.1136/bjsm.34.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Exercise dependence, social physique anxiety, and social support in experienced and inexperienced bodybuilders and weightlifters

Abstract: Objectives-To investigate psychological correlates of exercise dependence in experienced and inexperienced bodybuilders and weightlifters. Secondary objectives included measuring social physique anxiety, bodybuilding identity, and social support among bodybuilders and weightlifters. Methods-Thirty five experienced bodybuilders, 31 inexperienced bodybuilders, and 23 weightlifters completed the bodybuilding dependence scale, a bodybuilding version of the athletic identity measurement scale, the social physique a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
2
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 18 publications
4
40
2
11
Order By: Relevance
“…However a number of other studies have found no differences in AI between different sporting levels [e.g. 7,[8][9][10][11][12]. What appears to be a more consistent finding is an AI difference between individuals who participate in sport and those who do not.…”
Section: Introductionmentioning
confidence: 92%
“…However a number of other studies have found no differences in AI between different sporting levels [e.g. 7,[8][9][10][11][12]. What appears to be a more consistent finding is an AI difference between individuals who participate in sport and those who do not.…”
Section: Introductionmentioning
confidence: 92%
“…A escala correspondente ao sexo foi apresentada e questionada qual representaria respectivamente sua imagem atual e ideal. Várias revisões têm sugerido efetividade na determinação individual e do tipo corporal idealizado, sendo a discrepância entres estas duas medidas um forte indicativo de nível de insatisfação corporal 12 . A autoavaliação subjetiva dos distúrbios de imagem corporal é em geral, estimada pelo emprego de Escalas de Silhuetas compostas por figuras especialmente construídas para esta finalidade 20 .…”
Section: Casuísticaunclassified
“…No âmbito da pesquisa no Brasil já foi validado um questionário que avalia DEF em maratonistas 8 e suas repercussões negativas, tradicionalmente descritas na população de atletas principalmente em maratonistas 8,11 ; porém alguns outros trabalhos já foram realizados com fisiculturistas e levantadores de peso 12 ; praticantes de corrida de aventura 6 ; ultra maratonistas 13 e até mesmo em atletas de karatê estilo Shotokan 14 . Em relação a este último público já foi registrado que há tendência dos atletas de karatê Shotokan exibirem um perfil de comprometimento à prática relacionado ao estilo de vida, mais do que uma dependência propriamente dita, abrindo a perspectiva de que a DEF esteja relacionada ao tipo de exercício praticado, além de outras variáveis com tempo de atividade, intensidade, frequência etc 10,14,15 .…”
Section: Resumen Introducción: Las Artes Marciales Se Han Transformadunclassified
“…Several authors have been trying to understand this dimension of the identity concept since the 90´s (Brewer, 1993;Horton & Mack, 2000;Hurst et al, 2000;Martin, Mushet, & Smith, 1995;Smith, Hale, & Collins, 1998). The fi rst publications consider AI as a unidimensional construct defi ned it as the extent to which an individual identifi es him/herself with the role of the athlete (Brewer, Van Raalte, et al, 1993).…”
mentioning
confidence: 99%
“…They also report more positive experiences than those athletes with lower levels of athletic identity (Brewer, Van Raalte, & Linder, 1993;LamontMills & Christensen, 2006;Wiechman & William, 1997). However, this high level of AI may lead to an overinvolvement with sports practice, emotional diffi culties associated with career choice, humour disorders, substance abuse, unrealistic expectations regarding a sports related career and a lack of preparation for life and work outside of the sports world (Grove, Lavalle, & Gordon, 1997;Horton & Mack, 2000;Hurst, Hale, Smith, & Collins, 2000). The intensity of AI varies in association with past relationship to sports and current athletic experiences, as well as the athlete's personal experiences with athletic failures and successes (Horton & Mack, 2000).…”
mentioning
confidence: 99%